Comparative photoelectrochemical study of oligomeric s-heptazines nanomaterials derived from partial thermal decompositions of urea & thiourea precursors - Anupam Chowdhury; Dipanwita Majumdar; Moisilee Dutta; Swapan Kumar Bhattacharya (Materials Today Catalysis)
Thermal polymerization of urea and thiourea under closed conditions at 370 °C have been independently carried out and the derived samples were subjected to detailed characterization techniques that showed varied chemical compositions as well as distribution of functional groups despite the same C/N atomic ratio. The detailed optical, physicochemical and morphological characterizations from FTIR, RAMAN, XRD, TGA, XPS, solid-state & solution-state NMR, solid state UV–visible absorption, PL, BET, FESEM, TEM and SAED revealed that urea derived U370 sample with 2D flakes-like morphology closely resembles melem-cyanuric acid complex/adduct while thiourea derived T370 sample having flat ribbon-like structure can be intimately related with oligomeric melem (s-heptazines) hydrate respectively. Solution state UV–visible absorption spectroscopy, Zeta potential and Dynamic Light Scattering (DLS) aided size distribution studies were also conducted in aqueous media with varying pH to comprehend the character of chemical functionalities and nature of prevailing interactions in acid, neutral and alkaline electrolytes which were further be correlated with their photoelectrochemical responses. Their comparative electrochemical studies were conducted in aid with CV, GCD and EIS studies both under dark as well as in presence of different and wide range light sources in acid, neutral and basic media correspondingly to design low costing, eco-friendly, smart materials for light-driven supercapacitive devices. Results revealed T370 sample with better photoelectrochemical performance in terms of higher normalized areal capacitance, better rate capacity as well as improved cyclic stability than U370 sample in aqueous alkaline electrolyte. Thus, this communication outlines a novel approach for significantly upgrading the supercapacitive responses of materials using the simple aid of electromagnetic radiation, thereby opening up new roadways in the emerging field of photoelectrochemical charge storage and conversion technology.